Moral Teachings in the Manuscript of Qissatu Syamâun ibnu Khalid ibnu Walid - Supriadi, Dedi (ASPENSI in Bandung, Indonesia, 2016)
ABSTRACT: This article focuses on the moral teachings conveyed in the manuscript of QSKW (Qissatu Syamâun ibnu Khalid ibnu Walid or Story of Syamâun son of Khalid ibnu Walid). The manuscript of Â QSKW is written in Arabic language and is a manuscript which its stories are well-known in several version in Indonesia. As a fiction work, this manuscript cannot be separated from the narrative structure building the manuscript internally. The background of the birth of Islam and the struggle of Prophet Muhammad SAW (Salallahu Alaihi Wassalam or peace be upon him) affect significantly to the narrative structure of the QSKW manuscript, including the moral teachings delivered. The moral teachings can be analyzed with the method of Roland Barthes (2009)âs semiotics, namely with looking into the manuscript narration as signs showing meanings in two levels, that is âdenotativeâ and âconnotativeâ meanings. The result shows that the manuscript of QSKW contains Islamic values manifested into the moral teachings based on the holy book of Al-Qurâan and Hadiths (words and deeds of Prophet Muhammad). This shows also that the QSKW manuscript is an ancient manuscripts functioning as the teaching of the Islamic values in the aspects of âtawhidâ (acknowledge the oneness of God) and âakhlakâ (noble character). The background of the fictional story represents spirit and persistence of the âsahabasâ (companions of Prophet Muhammad) in depending Islam. Â KEY WORDS: Moral teaching, Islamic old manuscript, fictional story, Islamic values, and figure of Syamâun.About the Author: Dr. Dedi Supriadi is a Senior Lecturer at the Department of Arabic Language and Literature, Faculty of Adab and Humanities UIN (Universitas Islam Negeri or State Islamic University) Sunan Gunung Djati in Bandung, West Java, Indonesia. For academic interests, the author is able to be contacted via e-mail at: dedi70@yahoo.comHow to cite this article? Supriadi, Dedi. (2016). âMoral Teachings in the Manuscript of Qissatu Syamâun ibnu Khalid ibnu Walidâ in TAWARIKH: International Journal for Historical Studies, Vol.7(2) April, pp.157-172. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Chronicle of the article: Accepted (January 15, 2016); Revised (March 11, 2016); and Published (April 28, 2016).